2011
DOI: 10.1523/jneurosci.2597-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Preictal and Ictal Neurovascular and Metabolic Coupling Surrounding a Seizure Focus

Abstract: Epileptic events initiate a large focal increase in metabolism and cerebral blood flow (CBF) to the ictal focus. In contrast, decreases in CBF have been demonstrated surrounding the focus, the etiology of which is unknown i.e. arising either from active shunting of blood or passive steal. The relationship between these events and neuronal activity and metabolism are also unknown. We investigated neurovascular and neurometabolic coupling in the ictal surround using optical imaging of light scattering and cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
128
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(143 citation statements)
references
References 54 publications
13
128
2
Order By: Relevance
“…Reports have demonstrated that the localized application of GABA A antagonist BMI yields pronounced disinhibition, yielding increased excitatory signaling with consequent changes in metabolism and blood flow that vary with time and distance from the focal seizure location [54][55][56]. Studies continue to elucidate the specific details and mechanisms of focal seizure-induced neurovascular alterations in the center and surrounding areas [56,57]. Investigators have reported conflicting observations concerning the metabolic response to seizure activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have demonstrated that the localized application of GABA A antagonist BMI yields pronounced disinhibition, yielding increased excitatory signaling with consequent changes in metabolism and blood flow that vary with time and distance from the focal seizure location [54][55][56]. Studies continue to elucidate the specific details and mechanisms of focal seizure-induced neurovascular alterations in the center and surrounding areas [56,57]. Investigators have reported conflicting observations concerning the metabolic response to seizure activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Although the haemodynamic response is much longer than the electrographic assessment of seizure duration, it is remarkably consistent across seizure events, predominantly consisting of an initial increase, then prolonged decrease of blood volume. The reconstructed DOT images exhibit complex spatial dynamics reminiscent of a number of animal studies, which have shown an 'inhibitory surround' phenomenon associated with epileptic foci [18][19][20].…”
Section: Discussionmentioning
confidence: 91%
“…In both animal models and patients, the epileptic events can evoke drastic increases in CBF to meet the high metabolic demand caused by this intense neuronal activity. [9][10][11] Measures of oxygen partial pressure (PO 2 ) in tissue during seizures have displayed an initial dip with various methods 12,13 but the spatial landscape of this phenomenon has not been thoroughly documented. Recent data showed that most capillaries released little oxygen at baseline acting as an oxygen reserve that was recruited during increased neuronal activity.…”
Section: Introductionmentioning
confidence: 99%